2020
DOI: 10.1093/ve/veaa019
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs between host tolerances to different pathogens in plant–virus interactions

Abstract: Although accumulating evidence indicates that tolerance is a plant defence strategy against pathogens as widespread as resistance, how plants evolve tolerance is poorly understood. Theory predicts that hosts will evolve to maximize tolerance or resistance, but not both. Remarkably, most experimental works failed in finding this trade-off. We tested the hypothesis that the evolution of tolerance to one virus is traded-off against tolerance to others, rather than against resistance and identified the associated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…RTFL13 has been shown to be a regulator of flowering time that is expressed during cambium formation in Arabidopsis inflorescences [ 70 ]. There is ample evidence of the link between flowering time and the effect of virus infection on seed production [ 25 , 26 , 91 ]. Although the genetic bases are unknown, flowering genes are thought to control this process [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RTFL13 has been shown to be a regulator of flowering time that is expressed during cambium formation in Arabidopsis inflorescences [ 70 ]. There is ample evidence of the link between flowering time and the effect of virus infection on seed production [ 25 , 26 , 91 ]. Although the genetic bases are unknown, flowering genes are thought to control this process [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the development of plant symptoms in vegetative structures may potentially impact plant fitness and it is likely that both traits have genetic associations [ 10 ]. However, the effect of infection on plant growth and on plant reproduction are not necessarily linked, e.g., [ 20 , 25 , 26 ]. Hence, the host genetic determinants of virulence as the effect of virus infection on plant progeny production are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous experimental analyses have indicated that phenotypic structure for tolerance in animal and plant populations varies along a continuum from fixation (Roy et al ., 2000 ; Carr et al ., 2003 ; Lefèvre et al ., 2011 ) to no tolerance (Montes et al ., 2020 ), with a range of intermediate levels in between (Råberg et al ., 2007 ; Pagán et al ., 2008 ; Hayward et al ., 2014 ). It is thought that structure for tolerance can be maintained in the host population if tolerance has a cost in terms of host fitness or by reducing defences to other pathogens (Restif & Koella, 2003 ; Fornoni et al ., 2004 ; Vitale & Best, 2019 ), and evidence of such costs have been reported in several plant–pathogen (including virus) interactions (Simms & Triplett, 1994 ; Koskella et al ., 2002 ; Montes et al ., 2020 ). These observations strongly suggest that pathogens commonly face heterogeneous plant population structures for tolerance; yet analyses of pathogen evolution in response such structure are scant and sometimes contradictory, particularly for plant viruses.…”
Section: Introductionmentioning
confidence: 99%
“…TuMV is commonly found in wild populations of Arabidopsis, mostly in a single infection, at up to 60% prevalence (Pagán et al ., 2010 ), indicating that the Arabidopsis–TuMV interaction is significant in nature. TuMV infection affects Arabidopsis flower and silique viability, which may severely reduce plant fertility and often prevents reproduction (Sánchez et al ., 2015 ; Montes et al ., 2020 ). Also, virus infection greatly shortens plant lifespan (Vijayan et al ., 2017 ), and particularly the Arabidopsis reproductive period, thereby affecting progeny production (Montes et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%